2017
DOI: 10.1109/tnsre.2017.2693234
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Movement Analysis Framework to Study Upper Limb Function: A Pilot Study

Abstract: The functional capabilities of individuals with upper limb disabilities are assessed throughout rehabilitation and treatment regimens using functional outcome measures. For the upper limb amputee population, there are none which quantitatively take into account the quality of movement while an individual is performing tasks. In this paper, we demonstrate the use of an integrated movement analysis framework, based on motion capture and ground reaction force data, to capture quantitative information about how su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…As noted by Hebert et al[5, 6], allowing the subject to choose which blocks to move results in tremendous variability in the trajectories employed, making comparisons among subjects difficult. Previous work [11] has also found that the joint angle ranges and peak angle values observed during the BBT are much lower than those that have been reported from able-bodied subjects performing typical ADLs such as perineal care, drinking from a cup, lifting objects from the ground and off shelves[12], and carton pouring [13]. While it remains difficult to develop a single task that will evaluate every aspect of functional performance, modifications to existing outcome measures may increase their ecological validity, while still maintaining the benefits of ease and speed of implementation; reliable, objective measurement; and repetition of motion.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Hebert et al[5, 6], allowing the subject to choose which blocks to move results in tremendous variability in the trajectories employed, making comparisons among subjects difficult. Previous work [11] has also found that the joint angle ranges and peak angle values observed during the BBT are much lower than those that have been reported from able-bodied subjects performing typical ADLs such as perineal care, drinking from a cup, lifting objects from the ground and off shelves[12], and carton pouring [13]. While it remains difficult to develop a single task that will evaluate every aspect of functional performance, modifications to existing outcome measures may increase their ecological validity, while still maintaining the benefits of ease and speed of implementation; reliable, objective measurement; and repetition of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the targets can be correctly reached but with the help of compensatory movements (such as trunk flexion or rotation) that have to be avoided. Musculoskeletal pain and overuse injuries are actually a well-known problem for the upper-limb amputee population (Kontson et al, 2017 ; Postema, 2017 ). Error value of only concentrates on functional performance and does not take this point into account.…”
Section: Methodsmentioning
confidence: 99%
“…More specific aspects of motor control, such as compensatory movement, are less generalizable and therefore more difficult to predict. A number of studies have established range of motion (ROM) and maximum angle as joint specific measures of compensation [9,17,18]. In a study of myoelectric and BP prosthesis users, increased ROM was shown in the shoulder and trunk, suggesting compensation at these joints, compared to able-bodied controls [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of myoelectric and BP prosthesis users, increased ROM was shown in the shoulder and trunk, suggesting compensation at these joints, compared to able-bodied controls [9]. Similarly, reducing distal DOFs through bracing has also been shown to alter shoulder ROM and increase maximum angle [17]. Measuring the strain or work of individual joints may also be useful as a measure of a joint's relative contribution to movement or risk of overuse injury [19,20].…”
Section: Introductionmentioning
confidence: 99%